(untitled) (Architecture Image Studies, 2023)
Welcome to the first issue of the 2023 volume of Architecture Image Studies (AIS - V3, N1). This collection of articles embodies the journal’s commitment to exploring the ever-evolving relationship between architecture and the visual realm. In this issue, our authors take us on a captivating journey through a diverse array of topics, each offering unique insights into the multifaceted world of architectural imagery and design. Titled “Turkey Architecture Studies,” here are presented vibrant architectural discourses within this historically and culturally significant nation.